2011
DOI: 10.3109/01612840.2011.583810
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for Oblivion: Women's Experiences with Electroshock

Abstract: This article presents findings and analysis stemming from a two-year qualitative study that explored, in their own voices, women's lived experience of electroshock. Feminist standpoint theory frames and provides the moorings for both the validity and methodology of this woman-centered inquiry. In addition, nurses' experiences with and views of ECT are explored and compared to the experiences reported by the women recipients themselves. Vulnerability and disconnection as emergent themes are presented for the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
3
15
1
1
Order By: Relevance
“…Although relatively few qualitative studies have been conducted, all four of the published qualitative studies -and one published first person's account [11] -have reported persistent memory after ECT [12][13][14][15]. In addition, participants in these studies specifically attribute their memory loss to ECT, not to depression.…”
Section: Introductionmentioning
confidence: 99%
“…Although relatively few qualitative studies have been conducted, all four of the published qualitative studies -and one published first person's account [11] -have reported persistent memory after ECT [12][13][14][15]. In addition, participants in these studies specifically attribute their memory loss to ECT, not to depression.…”
Section: Introductionmentioning
confidence: 99%
“…Coercion does not necessarily mean bullying, but it can involve patients feeling that they cannot refuse or believing that there is no alternative to ECT and nurses using bribery regarding discharge outlook and future prospects or inveigling partners or other family member into promoting the expected positive results. Patients, given their vulnerability and desperation, will succumb and sign (Philpot et al, 2004;Van Daalen-Smith, 2011). On the other hand 86% of Rayner and colleagues (2009) 258 respondents agreed that they did not feel pressurized or forced.…”
Section: Nurses and Ect-related Responsibilitiesmentioning
confidence: 90%
“…Gaining informed consent is probably the most challenging process for the nurse, and vexing for patients, at least in retrospect (Philpot et al, 2004;Van Daalen-Smith, 2011). Finch (2005 in his ECT guide for nursing responsibilities claims it "is a dynamic process that is not completed with the signing of a formal document, but .…”
Section: Nurses and Ect-related Responsibilitiesmentioning
confidence: 99%
See 2 more Smart Citations